Nilai-nilai Moral yang Terkandung dalam Tasawuf Al-Ghazali dan Pengaruhnya terhadap Etika Islam - Widyastini Widyastini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2000)
This research aim is to know how far is the value of moral still being used by means of measurement in case of achieving human life happiness, especially in connection with God, human to human, and human to sicrumstances.When human without any bases on moral values, so the life of human will run imbalancely and more focus on his own needs than those society in general this case is based of princple;